If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15 + 7x + -5 + x = 0 Reorder the terms: 15 + -5 + 3x + 7x + x = 0 Combine like terms: 15 + -5 = 10 10 + 3x + 7x + x = 0 Combine like terms: 3x + 7x = 10x 10 + 10x + x = 0 Combine like terms: 10x + x = 11x 10 + 11x = 0 Solving 10 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 11x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 11x = 0 + -10 11x = 0 + -10 Combine like terms: 0 + -10 = -10 11x = -10 Divide each side by '11'. x = -0.9090909091 Simplifying x = -0.9090909091
| y=-9111*x^2+4E+07x-4e+10 | | 7p^2+16=21 | | x^2+-4x+2=0 | | y-5=2x+6 | | D=g+x/2 | | -7.0x-11.7=5.2x-10.4 | | (LN)33= | | (3x)-7=x+4 | | D=9+x/2 | | 4/5(m-1)-1/5m=1 | | 5x+20=6x+10 | | 5x+20=6x+19 | | -4x-6=-6x+11 | | 5x+6(8)=23 | | 2x-13=x-12 | | y+1/5=7/10 | | -3.1x-1.3=-3.2 | | 5x+10=2x-11 | | 2lx-2l=24 | | 11.37=4.52 | | x-2.3=1.8 | | 7(-2x+1)=13x+1 | | 6=k(30) | | b-6= | | 28=-8y | | 3/7x8/10 | | 9(8n+3)-(6n+4)=0 | | 2x(x+1)=2x^2+4 | | -57+-35= | | 33=-8y | | -48=6(v+s) | | 2x+(x+1)=2x^2+4 |